Encoding Equality: The Case for Greater Regulation of Artificial Intelligence and Automated Decision Making in New Zealand - Brownlie, Ella (Victoria University of Wellington Law Review, 2020)
Automated decision-making systems, developed using artificial intelligence and machine learning processes, are being used by companies, organisations and governments with increasing frequency. The purpose of this article is to outline the urgent case for regulating automated decision-making and examine the possible options for regulation. This article will argue that New Zealand's current approach to regulating decision-making is inadequate. It will then analyse art 22 of the European Union's General Data Protection Regulation, concluding that this regime also has significant flaws. Finally, this article will propose an alternative regulatory solution to address the novel challenge posed by automated decision-making. This solution aims to strike a balance between the interests of organisations in capitalising on the benefits of automated decision-making technology and the interests of individuals in ensuring that their right to freedom from discrimination is upheld.